SOSIALISASI PENINGKATAN SKIL MAHASISWA UNTUK MENUMBUHKAN KUALITAS CALON PENDIDIK DALAM MENJAGA LINGKUNGAN BERSIH, LINGKUNGAN SEHAT - Yetti S. Serkadifat; Lanny Wattimena; WindyWonmaly; Fitria Faderubu; Merlin Ruth Korwa (Yayasan Nusantara Hasana Berdikari, 2026)
Every activity of living things, every change in the physical, chemical, and biological characteristics of the environment, and every incident or event that results in environmental degradation, can be said to have the capacity to restore or improve the quality of the damaged environment. In recent years, it has been felt that the restoration and assimilation capacity of the biosphere is no longer as balanced as it was a few years ago. Natural systems have been operating and functioning for millions of years and are now beginning to show signs of stress, particularly due to the negative impacts of human activities on this environment. As the younger generation, we have a crucial role in maintaining a clean and healthy environment. However, many of us still lack the awareness and skills to protect the environment. Therefore, efforts are needed to increase the awareness and skills of the younger generation in maintaining a clean and healthy environment so as to encourage students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, and the Forestry Study Program, Faculty of Agricultural and Environmental Sciences, Victory University, Sorong, to conduct a socialization entitled